Do Digital Natives Recognize Digital Influence? Generational Differences and Understanding of Social Media Influencers. Issue 4 (2nd October 2021) - Childers, Courtney; Boatwright, Brandon
Abstract: Influencer marketing has upended traditional notions of endorsement, as advertisers partner with social media users with diverse followings but higher levels of engagement to reach key audiences. Twenty-five personal interviews were conducted with adults between the ages of 18 and 51 years to unearth shared experiences with and perceptions of influencer marketing efforts. Three key themes of difference between generational cohorts' perceptions of social media advertising and influencers (SMIs) were found: (1) digital natives and digital influence of social media advertising overall, (2) challenges associated with defining influencer marketing and understanding its impact, and (3) transparency and trust with influencers. The importance of community and connection in was a theme that emerged among all participants. This study broadens the framework for examining influencers' utility by providing implications for the advertising industry as well as for multidisciplinary research and practice.